The tetrapod fauna of the upper Permian Naobaogou Formation of China: 3. Jiufengia jiai gen. et sp. nov., a large akidnognathid therocephalian - Liu, Jun (2019)
Recent field trips to Member III of the Naobaogou Formation, Nei Mongol, China yielded new fossil discoveries, increasing our knowledge of the late Permian continental fauna from China. We present here a new large therocephalian, Jiufengia jiai gen. et sp. nov., represented by a partial skull with mandibles and part of the postcranial skeleton. This is the second therocephalian recovered from the Naobaogou faunal association and, in turn, the second akidnognathid from this unit and from China. The new taxon shows clear differences from Shiguaignathus wangi, the akidnogathid previously reported from the Naobaogou Formation: the presence of four upper postcanines, of a large suborbital vacuity, and the flat ventral surface of the vomer, lacking a ventromedian crest. Updating a previous phylogeny of therocephalians, we recover the new species as a basal member of Akidnognathidae, above a basal polytomy including the other two Laurasian akidnognathids, Shiguaignathus and Annatherapsidus, adding support to the hypothesis that this group originated in Laurasia.